Piezoelectric two-layer plate for position stabilization. (June 2014) - Krause, Martin; Steinert, Daniel; Starke, Eric; Marschner, Uwe; Pfeifer, Günther; Fischer, Wolf-Joachim
Numerous vibrating electromechanical systems lack a rigid connection to the inertial frame. An artificial inertial frame can be generated by a shaker, which compensates for vibrations. In this article, we present an encapsulated and perforated unimorph bending plate for this purpose. Vibrations can be compensated up to the first eigenfrequency of the system. As basis for an efficient system simulation and optimization, a new three-port multi-domain network model was developed. An extension qualifies the network for the simulation of the acoustical behavior inside the capsule. Network parameters are determined using finite element simulations. The dynamic behavior of the network model agrees with the finite element simulation results up to the first resonance of the system. The network model was verified by measurements on a laboratory setup, too. Furthermore, the network model could be simplified and was applied to determine the influence of various parameters on the stabilization performance of the plate transducer. The performance of the piezoelectric bending plate for position stabilization had been in addition investigated experimentally by measurements on a macroscopic capsule.